2020
DOI: 10.1080/15384101.2020.1802913
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of WNT2 in trophoblast cell behavior in preeclampsia development

Abstract: This study aimed to determine the WNT2 expression in patients with severe preeclampsia and to explore the function of WNT2 dysregulation on the biological behaviors of trophoblast cells. The WNT2 and β-catenin expression in the patients with early-onset and late-onset severe preeclampsia and normal controls was determined. Subsequently, WNT2 was overexpressed and knocked down in HTR8 cells and WNT2 signaling pathway in regulating trophoblast cell proliferation, migration, invasion, and apoptosis were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…These findings indicated the feasibility of using biomarkers as early predictors to discriminate pregnant women vulnerable to hypertensive events during pregnancy and estimation of serum levels of sEng can be used as a sole predictor and its level could predict the severity of PE. These results and assumption are in accordance with multiple recent studies evaluated various markers for prediction of vulnerability for developing PE during pregnancy [24,25,26] .…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicated the feasibility of using biomarkers as early predictors to discriminate pregnant women vulnerable to hypertensive events during pregnancy and estimation of serum levels of sEng can be used as a sole predictor and its level could predict the severity of PE. These results and assumption are in accordance with multiple recent studies evaluated various markers for prediction of vulnerability for developing PE during pregnancy [24,25,26] .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with prior literature showing that β-catenin transcriptionally represses early neural differentiation while activating markers for mesodermal differentiation in ESCs ( Davidson et al., 2012 ; Hoffmeyer et al., 2017 ). Less is known about β-catenin's importance for trophectoderm development, but a few studies have implicated β-catenin in successful trophoblast invasion and healthy placentation ( Fan et al., 2016 ; Liu et al., 2020b ). As cell-cell contact may change dramatically depending on the germ layer and embryonic stage, we hypothesize that dynamic regulation of β-catenin (mechanical or otherwise) may ensure proper specification of multiple tissues.…”
Section: Discussionmentioning
confidence: 99%
“…[247], Yu et al [248] and Li et al [249] showed that CYP2J2, BMPR1B, ROS1, SCN7A, WNT5A, HSD11B2, CYP24A1, WNK3, PPARGC1A, IGF1, OSR1, TLR3, BMP7, POSTN (periostin), ITGB3, THBS1, FLNA (filamin A), TRPC6, SELP (selectin P), VCL (vinculin), NOTCH2, F2RL3, LRP1, CLU (clusterin), SMAD3, PEAR1, MYH9, TGFB1, PDGFA (platelet derived growth factor subunit A), IL6R, TIMP1, TNFRSF1B, CD47, CD74, VCAN (versican), IRF7, NOTCH1, STIM1, CXCR4 and PDE5A expression can be associated with hypertension progression, but these genes might be novel targets for GDM. ROS1 [250], WNT2 [251], PHLDA2 [252], WNT5A [253], HSD11B2 [254], CLDN1 [255], CYP24A1 [256], HRG (histidine rich glycoprotein) [257], TLR3 [258], THBS1 [259], TRPC6 [260], SELP (selectin P) [261], CLU (clusterin) [262], CDKN1A [263], ITGB1 [264], HLA-E [265], IL6R [266], TIMP1 [267], SERPINA1 [268], CD74 [269], PANX1 [270], STIM1 [271] and CXCR4 [272] were revealed to be correlated with disease outcome in patients with preeclampsia. Previously reported studies have shown that the expression of LBP (lipopolysaccharide binding protein) [273], MC1R [274], CXCL14 [275], RGN (regucalcin) [276], NPY2R [277], MFAP5 [278], WNT5A [279], EDA (ectodysplasin A) [280], THSD7A [281], NEUROD1 [282], SLIT2 [283], PPARGC1A [219], IGF1 [144], OSR1 [284], TLR3 [285], BMP7 [286], POSTN (periostin) [287], LRP1B [288], THBS1 [289], NOTCH2 [290].…”
Section: Discussionmentioning
confidence: 99%
“…Polonikov et al [211], Chida et al [212], Yamada et al [213], Zhang et al [214], Kawarazaki et al [215], Ueda et al [216], Bao et al [217], Leng et al [218], Taghvaei et al [219], Norling et al [220], Brown et al [221], Singh et al [222], Liu et al [223], Nie et al [224], Liu et al [225], Sharma et al [226], Liu et al [227], Jain et al [228], Novoyatleva et al [229], Yu et al [230], Sahoo et al [231], Gamboa et al [232], Zeng et al [233], Zabini et al [234], Olivi et al [235], Liu et al [236], Nabrdalik et al [237], Katayose et al [238], Topchieva et al [239], Onal et al [240], Speirs et al [241], Novelli et al [242], Le Hiress et al [243], Chang et al [244], Deng et al [245], Wang et al [246], Dhande et al [247], Yu et al [248] and Li et al [249] showed that CYP2J2, BMPR1B, ROS1, SCN7A, WNT5A, HSD11B2, CYP24A1, WNK3, PPARGC1A, IGF1, OSR1, TLR3, BMP7, POSTN (periostin), ITGB3, THBS1, FLNA (filamin A), TRPC6, SELP (selectin P), VCL (vinculin), NOTCH2, F2RL3, LRP1, CLU (clusterin), SMAD3, PEAR1, MYH9, TGFB1, PDGFA (platelet derived growth factor subunit A), IL6R, TIMP1, TNFRSF1B, CD47, CD74, VCAN (versican), IRF7, NOTCH1, STIM1, CXCR4 and PDE5A expression can be associated with hypertension progression, but these genes might be novel targets for GDM. ROS1 [250], WNT2 [251], PHLDA2 [252], WNT5A [253], HSD11B2 [254], CLDN1 [255], CYP24A1 [256], HRG (histidine rich glycoprotein) [257], TLR3 [258], THBS1 [259], TRPC6 [260], SELP (selectin P) [261], CLU (clusterin) [262], CDKN1A [263], ITGB1 [264], HLA-E [265], IL6R [266], TIMP1 [267], SERPINA1 [268], CD74 [269], PANX1 [270], STIM1 [271] and CXCR4 [272] were revealed to be correlated with disease outcome in patients with preeclampsia. Previously reported studies h...…”
Section: Discussionmentioning
confidence: 99%